Residual bone level as a prognostic factor in the surgical treatment of peri-implantitis - Martin-Cabezas, Rodrigo; Giannopoulou, Catherine (Frontiers in Dental Medicine, 2024)
Peri-implantitis is a progressive inflammatory disease affecting the tissues surrounding dental implants and leading to bone loss. The severity of this disease is typically classified based on the depth of the bone defect or the percentage of bone loss around the implant. Marginal bone loss is a critical factor in the surgical management of peri-implantitis, as it can complicate access for implant decontamination and hinder efforts to stabilize the condition. In cases where bone loss exceeds 50% of the implant length, explantation is often recommended due to significantly reduced success rates after treatment. This narrative review seeks to examine the scientific evidence on marginal bone loss as a prognostic factor in the surgical treatment of peri-implantitis.